范晔《后汉书》“论”、“赞”研究 = Study on Lun and Zan of Fan Ye's History of Eastern Han - 关天辰 Guan, Tianchen (2014)
“论”、“赞”皆是史书中重要的体例，表达官 皆是史书中重要的体例，表达官 史学观念的重要渠道，亦 史学观念的重要渠道，亦 是映射著书之人文学功底的一面明镜。在中国前四史，惟《后汉》因范晔 是映射著书之人文学功底的一面明镜。在中国前四史，惟《后汉》因范晔 是映射著书之人文学功底的一面明镜。在中国前四史，惟《后汉》因范晔 是映射著书之人文学功底的一面明镜。在中国前四史，惟《后汉》因范晔 是映射著书之人文学功底的一面明镜。在中国前四史，惟《后汉》因范晔 谋反被诛而鲜有人问津。但范晔无论在史学还是文上，都对后世着巨大的 谋反被诛而鲜有人问津。但范晔无论在史学还是文上，都对后世着巨大的 谋反被诛而鲜有人问津。但范晔无论在史学还是文上，都对后世着巨大的 贡献。本文将以《后汉书》中个别列传的 论赞进行研究，探讨贡献。本文将以《后汉书》中个别列传的 论赞进行研究，探讨贡献。本文将以《后汉书》中个别列传的 论赞进行研究，探讨贡献。本文将以《后汉书》中个别列传的 论赞进行研究，探讨贡献。本文将以《后汉书》中个别列传的 论赞进行研究，探讨贡献。本文将以《后汉书》中个别列传的 论赞进行研究，探讨贡献。本文将以《后汉书》中个别列传的 论赞进行研究，探讨贡献。本文将以《后汉书》中个别列传的 论赞进行研究，探讨贡献。本文将以《后汉书》中个别列传的 论赞进行研究，探讨贡献。本文将以《后汉书》中个别列传的 论赞进行研究，探讨特色及对前人的突破。 Lun and Zan are both valuable and indispensable parts of Chinese historical records, which provide a gateway to express the author's views, and also reflect the author's compiling capability. Among Early Four Historiographies, the value of Fan Ye's History of Eastern Han has always been underestimated due to the fact that he was announced to be a rebel. Yet Fan Ye has done remarkable contribution in both historiography and literature, especially his Lun and Zan in the History of Eastern Han. The thesis will analyze the characteristics of selected Lun and Zan from History of Eastern Han, and study on how Fan Ye had made a significant breakthrough in historiography and literature.